Analisis Yuridis Tindak Pidana Perzinaan Berdasarkan Pasal 284 Kitab Undang-Undang Hukum Pidana Dalam Perspektif Hukum Pidana Dan Hukum Pidana Islam - Yudhistira Nugraha; Dessy Artina; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Pancasila as the basis, ideology, and philosophy of the nation consists of five precepts, the first andforemost precepts are the precepts of the One Godhead. the interpretation of Article 29 paragraph (1) of the1945 Constitution has six interpretations, three of which include the formation of law in Indonesia, everystatutory regulation in Indonesia must not conflict with Islamic law for Muslims including the inheritance ofthe Criminal Code (KUHP) The Netherlands contained in Article 284 of the Criminal Code concerningAdultery Crimes is contrary to the teachings of Islam. This study entitled "Juridical Analysis of AdulteryCrimes Based on Article 284 of the Criminal Code in the Perspective of Criminal Law and Islamic CriminalLaw. Having the formulation of the problem What is the crime of adultery in the perspective of CriminalLaw and Islamic Criminal Law, What are the weaknesses of the formulation of Article 284 of the PenalCode concerning criminal acts of adultery? Islamic Criminal Law and Pancasila.The method in this study is normative legal research or the literature includes research on legalprinciples, legal systematics, vertical and horizontal synchronization, legal comparison, and legal history.In this case, the researcher discusses the comparison of laws, the comparison aims to provide knowledgeabout the similarities and differences between various fields of legal governance and basic understanding.Have conclusions. First, the regulation of criminal acts of adultery in criminal law is clearly not inaccordance with the life of the community and the order of the scope of the law in the social life of thecommunity at this time, or in other words not in accordance with the values of the Pancasila. second, theweaknesses contained in Article 284 of the Criminal Code, the problem generally lies in imprisonmentsanctions that are so light that only 9 (nine) months imprisonment for the perpetrators of zina crime. Third,imprisonment sanctions and fine criminal sanctions in the 2018 Criminal Code Bill look so light. So thatwhat we know is the criminal sanctions fined in the 2018 Criminal Code Bill, is not enough to seizeindependence from criminal offenders.The author's suggestion, first, needs to be transformed Islamic legal values and values in Pancasila asessentially the State of Law, into the formulation of zina offenses and criminal sanctions in the framework ofconstructing thoughts on Article 284 concerning zina crime in renewing criminal law in the context ofcriminal law policy . Second, public awareness of the most important and main laws in dealing with zinacrimes, if not regulated in the Criminal Code, the public must know that criminal acts of adultery areregulated and strictly prohibited in Islamic law. Third, the State must immediately design and accelerate thesteps, in the drafting of the Laws and Regulations on the Criminal Code (KUHP Bill) which Indonesianpeople aspire to.Keywords : Crime - Adultery - Criminal Law - Islamic Criminal Law